The Cross‐cultural Transportability of Situational Judgment Tests: How does a US‐based integrity situational judgment test fare in Spain?. (December 2015) - Lievens, Filip; Corstjens, Jan; Ángel Sorrel, Miguel; Abad, Francisco José; Olea, Julio; Ponsoda, Vicente
Abstract : Despite the globalization of HRM, there is a dearth of research on the potential use of contextualized selection instruments such as situational judgment tests (SJTs) in other countries than those where the selection instruments were originally developed. Therefore, two studies are conducted to examine the transportability of an integrity SJT that was originally developed in the United States to a Spanish context. Study 1 showed that most SJT scenarios (16 out of 19) that were developed in the United States were also considered realistic in a Spanish context. In Study 2, the item option endorsement patterns converged to the original scoring scheme, with the exception of two items. In addition, there were high correlations between the original US empirical scoring scheme and two empirical scoring schemes that were tailored to the Spanish context (i.e., mode consensus scoring and proportional consensus scoring). Finally, correlations between the SJT integrity scores and ratings on a self‐report integrity measure did not differ significantly from each other according to the type of scoring key (original US scoring vs. Spanish scoring keys). Overall, these results shed light on potential issues and solutions related to the cross‐cultural use of contextualized selection instruments such as SJTs.